Simulation of Determination of Positioning Errors of a Robotic Manipulator - Wojciech LISOWSKI (Communications of International Proceedings, 2025)
Credible assessment of positioning errors of industrial robots is important for their application. The paper concerns a problem of determination of positioning errors of a manipulating robot basing on simulated experimental results. The procedure of ISO 9283 standard was the base of determination of 5 measurement points. A suggested set containing 9 points was also used. Kinematic DH model of a manipulator was applied to determine the measurement points. Actual poses were obtained by introduction of small arbitrarily selected changes to parameters of the nominal kinematic model. Simulated measurement results were obtained by modification of actual coordinates by adding pseudorandom errors. Determination of the positioning error was preceded by alignment of the robot base frame to the instrument coordinate frame. Next, the positioning errors were calculated with respect to the aligned base frame. An attempt to improve the initial results consisted in an iterative updating of the alignment using results of zero joint coordinates offsets estimation. In the result of the simulation, the average error of estimation of the positioning error in 9 points was reduced from about 65% to about 7%. The simulation results confirmed that erroneous alignment of the robot base frame to the instrument frame significantly influenced accuracy of determination of the positioning error, and that this accuracy might be improved by iterative updating of the joint coordinates values with the estimated zero joint offsets.
Keywords: industrial robots; robotic manipulator; robot positioning errors